Asset Pricing with Limited Risk Sharing and Heterogeneous Agents - Gomes, Francisco; Michaelides, Alexander (Review of Financial Studies, 2008)
1 We solve a model with incomplete markets and heterogeneous agents that generates a large equity premium, while simultaneously matching stock market participation and indi-vidual asset holdings. The high risk premium is driven by incomplete risk sharing among stockholders, which results from the combination of aggregate uncertainty, borrowing con-straints and a (realistically) calibrated life-cycle earnings profile subject to idiosyncratic shocks. We show that it is challenging to simultaneously match asset pricing moments and individual portfolio decisions, while limited participation has a negligible impact on the risk premium, contrary to the results of models where it is imposed exogenously. JEL Classification: G11, G12.